Subjective economic wellbeing of students of youthful age - Fofanova, Galina A.; Gavrilchik, Ekaterina V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes the approaches to the concept of subjective economic well-being, the features of subjective economic well-being of students of youthful age are described and interpreted. It was found that students, in general, satisfied with their economic well-being, but they are characterized by negative financial expectations for the future. Male students tend to evaluate their economic well-being higher than women. Location has also a certain influence on subjective economic well-being of students: in a small town largely observed adverse financial expectations. Increased experience of independent economic behavior leads to a decrease of the level of economic optimism.
Keywords: subjective economic well-being; factors of the subjective economic well-being; ubjective economic wellbeing of students; economic optimism; economic anxiety